DETERMINING THE RESERVES FOR REDUCING THE COST OF LIVESTOCK PRODUCTS AND IMPROVING THE QUICK ANALYSIS METHOD (Ustozlar uchun, 2025)
The article studies methods for determining and express analysis of reserves for reducing the cost of livestock products. A conclusionwas formulated and proposals were made to reduce the cost of livestock products and improve the express analysis method.